The effect of unpredictable early childhood environments on parenting in adulthood. [article]. - Szepsenwol, Ohad; Simpson, Jeffry A.; Grislevicius, Vladas; Lee, Raby K.
Life history theory suggests that individual differences in parenting are partially rooted in environmental conditions experienced early in life. Whereas certain conditions should promote increased investment in parenting, unpredictable and/or harsh environments should promote decreased investment in parenting, especially in men. We tested this hypothesis in 3 studies. In Study 1a, we conducted analyses on 112 parents taking part in the Minnesota Longitudinal Study of Risk and Adaptation (MLSRA), all of whom have been continuously studied starting before they were born. Parenting orientations were assessed at age 32 via an interview. Findings showed that experiencing more unpredictability at ages 0-4 (i.e., frequent changes in parental employment status, cohabitation status, and residence) prospectively forecasted more negative parenting orientations among men, but not women. This effect was serially mediated by lower early maternal supportive presence measured at ages 0-4 and insecure attachment assessed at ages 19 and 26. In Study 1b, we replicated these findings on 96 parents from the MLSRA using behavioral observations of their parental supportive presence. In Study 2, we replicated the effect of early-life unpredictability on men's parenting orientations with a sample of 435 parents. This effect was mediated by adult attachment anxiety and avoidance. Across all studies, greater early-life harshness (low socioeconomic status [SES]) did not predict adult parenting outcomes. These findings suggest that greater early-life unpredictability may be conveyed to children through less supportive parenting, which results in insecure attachment representations in adulthood. Among men, this process culminates in less positive adult parenting orientations and less supportive parenting. -- (from the authors)